Effects of oligofructose-enriched inulin addition before and after the extrusion process on the quality and postprandial glycemic response of corn-snacks - Capriles, Vanessa D.; Conti-Silva, Ana Carolina [UNESP]; Gomes Arêas, José Alfredo (Elsevier, 2021)
Extruded snacks often have a high energy density and high lipid content, along with low fibre content and high glycemic impact. So, enrichment with dietary fibre has the potential to improve the nutritional status of these popular products. In this study, the effects of enrichment with inulin-type fructans (ITFs), both before and after the extrusion process, on the physical characteristics, sensory acceptance, nutrient profile, and postprandial glycemic response of corn-snacks were assessed. The addition of 13.3% oligofructose-enriched inulin resulted in a snack with 4 g of ITFs/30 g serving size, having no effects on expansion but reducing the cutting force and increasing the fibre level by sevenfold compared to the control product. ITFs-enriched snacks were acceptable, with scores for flavour, crunchiness and overall liking of approximately 7.0 on a 9-point hedonic scale. The enrichment of snacks with 13.3% ITFs either before or after the extrusion process caused the same statistical reduction of the glycemic index (81 to 71) and glycemic load (21 to 14), yielding a product that combines high-quality and acceptance with a substantial supply of prebiotic dietary fibre and a medium glycemic load. Both approaches are promising alternatives for meeting the consumer demand for new healthy ready-to-eat-products.
Keywords: Dietary fibre; Glycemic index; Glycemic load; Oligofructose-enriched inulin; Sensory acceptance